Wage Convergence and Inequality after Unification: (East) Germany in Transition - Johannes Gernandt; Friedhelm Pfeiffer (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2008)
This paper investigates the wage convergence between East German workers and their West German counterparts after reunification. Our research is based on a comparison of three groups of workers defined as stayers, migrants and commuters to West Germany, who lived in East Germany in 1989, with groups of West German statistical twin workers, all taken from the Socio-Economic Panel (SOEP). According to our findings, wage convergence for stayers is roughly 75 percent and for commuters 85 percent. Wages of migrants to West Germany equal the ones of their West German statistical twins. We conclude that labor markets in East and West Germany are still characterized by wage differences but that the degree of inequality in both regions converged.
Keywords: J30; J31; J61; 330; Wage convergence; wage inequality; German unification; migration; commuting; Regionale Lohnstruktur; Wirtschaftliche Anpassung; Entwicklungskonvergenz; Regionale Arbeitsmobilität; Neue Bundesländer; Alte Bundesländer; Deutschland